A Before-School Physical Activity Intervention to Improve Cognitive Parameters in Children: The Active-Start Study - Fernandez-Vergara, O; Garcia-Hermoso, A; Gonzalez-Calderon, N; Hormazabal-Aguayo, I (Blackwell Munksgaard, 2020)
The aim of the study was threefold: (a) to test a before-school physical activity intervention (Active-Start) on academic performance, selective attention, and concentration capacity; (b) to test the effect of the Active-Start intervention on anthropometry, body composition, and physical fitness parameters; and (c) whether the physical fitness components are moderators of the effect of the Active-Start program on academic performance, selective attention, and concentration capacity in Chilean children. The Active-Start intervention was a RCT which comprised 170 children (8-10 years old) from three public schools with low socioeconomic status from the city of Santiago (Chile). The exercise intervention was delivered daily, before starting the first school-class (8:00-8:30 am) for 8 weeks. Changes in academic performance, selective attention and concentration capacity, anthropometric, body composition, and physical fitness parameters were measured. The analyses used were mixed regression models for repeated measures over time. No statistically significant changes in attention and concentration capacity were found. However, significant changes were seen in language (0.63; 95% CI 0.49-0.77) and mathematics (0.49; 95% CI 0.32-0.66) performance (P <.001). Also, improvements were seen in fat mass, fat-free mass, muscular, and cardiorespiratory fitness (all P <.05). The Johnson-Neyman technique revealed a significant relationship between the effect of intervention and attention and concentration when change in cardiorespiratory fitness was above, but not below, 3.05 and 0.70 mL/kg/min, respectively. Implementing before-school physical activity programs such as the Active-Start to enhance the cardiorespiratory fitness may benefit attention capacity and academic success among schoolchildren. © 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd